1990
DOI: 10.1002/jnr.490250316
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide: A neurotrophic releasing agent and an astroglial mitogen

Abstract: Vasoactive intestinal peptide (VIP) increases neuronal survival in dissociated spinal cord cultures during a critical period of development. In the present study, two mechanisms contributing to this action of VIP have been observed: 1) VIP was shown to be a secretagogue for neuron survival-promoting activity; and 2) VIP was found to be an astroglial mitogen. A high molecular weight substance (greater than 30 kDa), which increased neuronal survival in tetrodotoxin (TTX)-treated spinal cord cultures, was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 182 publications
(87 citation statements)
references
References 37 publications
3
84
0
Order By: Relevance
“…ADNP mRNA is regulated by VIP (Bassan et al, 1999), and here we demonstrate that incubation with VIP resulted in higher levels of ADNP-like immunoreactivity in conditioned media from astrocytes. VIP is known to produce a neurotrophic milieu (Brenneman et al, 1990;Gozes et al, 1991;Waschek, 1995;Brenneman and Gozes, 1996;Gressens, 1999;Brenneman et al, 2003), and it has been suggested that ADNP constitutes part of this protective environment. However, it is unclear whether ADNP is released into the medium by a constitutive or regulated process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADNP mRNA is regulated by VIP (Bassan et al, 1999), and here we demonstrate that incubation with VIP resulted in higher levels of ADNP-like immunoreactivity in conditioned media from astrocytes. VIP is known to produce a neurotrophic milieu (Brenneman et al, 1990;Gozes et al, 1991;Waschek, 1995;Brenneman and Gozes, 1996;Gressens, 1999;Brenneman et al, 2003), and it has been suggested that ADNP constitutes part of this protective environment. However, it is unclear whether ADNP is released into the medium by a constitutive or regulated process.…”
Section: Discussionmentioning
confidence: 99%
“…They receive signals from neighboring neurons and respond to these signals with the release of neuroactive substances (Brenneman et al, 1990;Gozes et al, 1991;Araque et al, 1999;Fields and Stevens-Graham, 2002). Vasoactive intestinal peptide (VIP) released from neurons (Martin and Magistretti 1989a;Martin and Magistretti 1989b;Brown, 2000) stimulates glia to generate neurotrophic factors including activity-dependent neurotrophic factor , protease nexin-1 (Houenou et al, 1995), interleukin-1, interleukin-3, granulocyte colony stimulating factor, tumor necrosis factor-α, macrophage colony stimulating factor and interleukin-6 (Brenneman et al, 1992;Brenneman et al, 1995;Brenneman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, VIP appears to be inhibitory or stimulatory in function of the model studied. It stimulated cell proliferation in mouse astroglial cells (Brenneman et al, 1990), whereas it inhibited proliferation in others, like the human neuroblastoma IMR 32 (O'Dorisio et al, 1992) and the T98G glioblastoma . A lipophilic VIP analog, stearyl-Nleu(17)-neurotensin (6-11)-VIP (7-28), enhanced the antiproliferative effect of chemotherapeutic agents, such as doxorubicin, cisplatine, and vinorelbine, on advanced solid tumors, such as nonsmall cell lung carcinoma, colon carcinoma, or prostate carcinoma (Gelber et al, 2001).…”
Section: Journal Of Molecular Neurosciencementioning
confidence: 97%
“…VIP has been shown to interact with high affinity receptors present on glial cells (17), resulting in the release of survivalpromoting substances (18,19), among which are a glial-derived cytokine (IL-1-␣ references 8,20), and protease nexin I, a serine protease inhibitor (21). However, the neuronal survivalpromoting effects of the VIP-conditioned medium were observed at very low concentrations that could not be attributed to IL-1 or protease nexin I released from astroglia.…”
Section: Introductionmentioning
confidence: 99%
“…The ADNF secretagogue, VIP, has been shown to prevent neurotoxicity associated with the HIV envelope protein (GP120, reference 22) as well as against neurotoxicity associated with the beta amyloid peptide which is deposited in the brains of Alzheimer's disease patients (23). The mechanisms of these VIP effects are probably due to its ability to promote the secretion of neuroprotective substances from glial cells (18)(19)(20)(21). Here, we test the hypothesis that VIP's neuroprotective actions are mediated in part through ADNF.…”
Section: Introductionmentioning
confidence: 99%